Implementation of Learning of The Akidah Akhlak In The Character of Loving The Country - Alimni Alimni (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: Implementation of Learning of The Akidah Akhlak In The Character of Loving The Country.The purpose of this research is to describe the implementation of Akidah Ahlak learning to form the character of love for the homeland at Madrasah Ibtidaiyah. This type of research is descriptive qualitative, because the primary data are 4th grade students, and secondary data are teachers of morals and the principal of the school. Methods of data collection using the method of observation, interviews, documentation. The results of this study indicate that Public Madrasah Ibtidaiyah 04 Seluma has introduced character education to love the homeland through the study of moral creed. Although there are several obstacles, the teacher provides solutions to minimize these obstacles. So that the implementation of Akidah Akhlak Learning in to form of the Character of Love for the Homeland goes well. The attitude of love for the homeland is reflected in how we defend our homeland, are ready to sacrifice for the nation and state, love customs, culture, language and preserve nature and the environment.Abstract: Penerapan Model Pembelajaran Mastery Learning (Belajar Tuntas) dalam Meningkatkan Prestasi Belajar Akidah Akhlak.Tujuan penelitian ini untuk mendeskripsikan Implementasi Pembelajaran Akidah Ahlak alam membentuk karakter cinta tanah air pada Madrasah Ibtidaiyah. Jenis penelitian ini adalah deskriptif kualitatif, karena data primernya adalah siswa kelas IV, dan data sekundernya adalah guru mata pelajaran akidah akhlak dan kepala sekolah. Metode pengumpulan data menggunakan metode observasi, wawancara, dokumentasi. Hasil penelitian ini menunjukan bahwa Madrasah IbtidaiyahNegeri 04 Seluma telah memperkenalkan pendidikan karakter cinta tanah air melalui kajian akidah akhlak, walaupun terdapat beberapa kendala, namun guru memberikan solusi untuk meminimalisir kendala tersebut. Sehingga Implementasi Pembelajaran Akidah Akhlak Dalam Pembentukan Karakter Cinta Tanah Air berjalan dengan baik. Sikap cinta tanah air tercermin dari bagaimana kitamempertahankan tanah air kita, siap berkorban demi bangsa dan negara, mencintai adat istiadat, budaya, bahasa dan melestarikan alam dan lingkungan.